FAMILY COMMUNICATION AND CONFLICT DURING ADOLESCENCE - Parra Jiménez, Águeda; Oliva Delgado, Alfredo (Anales de Psicología / Annals of Psychology, 2002)
The aim of this paper is to study the pattern of family communication and conflict during adolescence. A sample of 221 boys and 292 girls aged between 13 and 19, were surveyed about frequency of communication with both parents, frequency of conflicts, emotional intensity of these conflicts and their functional autonomy. The article presents some interesting results. On the one hand it reflects a less negative and less conflictive image of adolescence, due adolescents stating that they do not argue with their parents frequently. On the other hand, our results show important gender differences: girls talk more with their parents, have less arguments with them and are less autonomous than boys. Through adolescence, frequency of family conflict decreases slightly, and family communication increases, mainly for girls. Finally, our results identify an interesting relationship between frequency of conflictand emotional intensity.